PELATIHAN LITERASI KEUANGAN UNTUK MENINGKATKAN PEMAHAMAN PENGELOLAAN KEUANGAN DI KALANGAN KARYAWAN PERUSAHAAN RITEL KOTA PEKANBARU (STUDI PADA CV. METROPOLITAN) - Andira, Agung Putra; Wongso, Fery; Chandra, Roni; Pendi, Irwansyah; Silaban, Yoga Samuel (Komunitas Manajemen Kompetitif, 2024)
. The purpose of this study is to find out and analyze the marketing mix, service quality, electronic word of mouth (EWOM) affect students' interest in choosing a vocational high school. To find out and analyze the marketing mix, service quality and electronic word of mouth (EWOM) affect students' decisions in choosing vocational high schools. To find out and analyze interest affects students' decisions in choosing vocational high schools. all vocational high school (SMK) students in Riau Province as many as 104,035 students from 13 districts/cities. The data used in this study are primary data and secondary data, while the data collection technique uses a questionnaire. The data analysis technique used in this study is Structural Equation Modeling (SEM). The results of the service quality research, electronic word of mouth (EWOM) have an effect on student interest. The mix of marketing, service quality and electronic word of mouth (EWOM) affects students' decisions. Interest affects student decisions. And the mix of marketing, service quality and electronic word of mouth (EWOM) affects students' decisions through interest.